UPAYA MENANAMKAN NILAI NILAI ENTERPRENEURSHIP KEPADA SISWA MELALUI BUDAYA SEKOLAH - Anggreani, Elyza; Husmita, Desy (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract—. This study aims to determine the efforts of schools to instill awareness of the importance of entrepreneurship for young people in welcoming the Asean Economic Community (AEC) and the industrial revolution 5.0. The research site was conducted at Sekayu 5 Public Middle School. This research uses a descriptive qualitative approach. Data collection techniques can be done by observation, interviews, and documentation. In qualitative research, data collection uses observation, interviews, documentation and literature study. The analysis technique uses qualitative analysis techniques which include data reduction, data presentation and drawing conclusions. The results of the study stated that the efforts of Sekayu 5 Public Middle School to instill the value of entrepreneurship consisting of 1) independent; 2) creative; 3) dare to take risks; 4) action oriented; 5) leadership; 6) honesty, and 7) hard work, which is integrated through school culture. School efforts to instill the value of entrepreneurship to students through school culture are carried out by setting an example, continuously managing and being conditioned so that they can instill the value of entrepreneurship to students of Sekayu 5 Middle School. Keywords— Value of Entrepreneurship, School Culture Abstrak— penelitian ini bertujuan untuk mengetahui upaya sekolah menanamkan kesadaran akan pentingnya karakter enterpreneurship bagi generasi muda dalam menyambut  Masyarakat Ekonomi Asean (MEA) dan revolusi industri 5.0. Tempat penelitian dilaksanakan di SMP Negeri 5 Sekayu. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data dapat dilakukan dengan observasi, wawancara, dan dokumentasi. Dalam penelitian kualitatif, pengumpulan data menggunakan observasi, wawancara, dokumentasi dan studi pustaka. Teknik analisis menggunakan teknik analisis kualitatif  yang meliputi reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menyatakan bahwa upaya SMP Negeri 5 Sekayu untuk menanamkan nilai nilai entrepreneurship yang terdiri dari 1) mandiri; 2) kreatif; 3) berani mengambil resiko; 4) berorientasi pada tindakan; 5) kepemimpinan;  6) kejujuran, dan 7) kerja keras, yang diintegrasikan melalui budaya sekolah. upaya sekolah menanamkan nilai nilai entrepreneurship kepada siwa melalu budaya sekolah dilakukan dengan membentuk keteladanan, terus menurus dan dikondisikan agar dapat menanamkan nilai nilai entrepreneurship kepada siswa SMP Negeri 5 Sekayu. Kata Kunci— Nilai Nilai Enterpreneurship, Budaya Sekolah